Corporate philanthropic giving, advertising intensity, and industry competition level - ZHANG, Ran (Institutional Knowledge at Singapore Management University, 2010)
This article examines whether the likelihoodand amount of firm charitable giving in response tocatastrophic events are related to firm advertising intensity,and whether industry competition level moderatesthis relationship. Using data on Chinese firms’ philanthropicresponse to the 2008 Sichuan earthquake, we findthat firm advertising intensity is positively associated withboth the probability and the amount of corporate giving.The results also indicate that this positive advertisingintensity-philanthropic giving relationship is stronger incompetitive industries, and firms in competitive industriesare more likely to donate. This study thus provides evidencesuggesting that even in the wake of catastrophicevents, corporate philanthropic giving is strategic.